Development of a Noble Moral Assessment Instrument for Human Moral Dimensions for High School Students - Rahayu Retnaningsih; Anton Sri Budaya; Saryanto Saryanto; Anesito L Cutillas; Froilan D Mobo (Universitas Negeri Malang, 2024)
The purpose of this study was to obtain the instrument construction, determine the validity and reliability of the instrument, obtain the instrument results, determine the effectiveness of the noble moral assessment instrument of the human moral dimension that has been developed for high school students in Klaten Regency. This study is a development research. The subjects in this study were class X students of SMA Negeri 1 Klaten, SMA Negeri 1 Karanganom, SMA Negeri 1 Wedi. With a total of 818 students. Data analysis used includes Exploratory Factor Analysis, reliability analysis using Cronbach's Alpha and descriptive analysis. The results of the study showed (1) The assessment of human noble morals carried out by teachers has not used valid and reliable instruments. (2) The construction of the noble moral assessment instrument in humans consists of: prioritizing similarities with others, respecting differences, cognitive empathy, emotional empathy, social empathy, therapeutic empathy, moral empathy, virtual empathy, cultural empathy, with the self-assessment (SA) model. (3). The indicators formed for the development of noble moral assessments in humans are 7 in number with a total of 36 items. (4). The validity of the assessment instrument content from expert validation by 9 experts, and continued with the calculation of the Aiken index.